Liberia : Strategic Policy Options for Medium Term Growth and Development - World Bank (Washington, DC, 2013)
This paper explores Liberia's policy options in support of the development of a Medium-Term Growth and Development Strategy (MTGDS) for 2013-2017 and its national vision, Liberia Rising 2030. At issue is the mismatch between available fiscal space and the enormous development needs that the government must resolve as it prepares to transform the economy into a middle-income country by 2040. This dilemma calls for the new administration to make trade-offs among various priorities if it is to achieve its aspirations. For this purpose, a Liberian version of a single-country Computable General Equilibrium (CGE) model, MAMS (Maquette for Millennium Development Goal, or MDG simulations), was developed and informed by analytical studies as well as sector strategies prepared in support of Liberia's MTGDS. This paper examines the likely impacts on macroeconomic and social indicators of alternate strategic policy scenarios. A base scenario (designed to represent a central case for the evolution of Liberia's economy up to 2030) was first established, and thereafter a set of different assumptions were introduced for the mining sector, government spending on infrastructure and human development, and foreign borrowing. The paper is organized into five sections including this introduction. Section two presents the basic features of MAMS. The simulation analysis, which is the focus of the paper, is covered in the next two sections: the base scenario in section three and a set of alternative scenarios, which are contrasted with the base scenario, in section four. The final section summarizes the main findings and conclusion. Appendices one and two include a set of figures with selected simulation results and a brief discussion of the Liberian database for MAMS, respectively.